1986
DOI: 10.1007/bf01407449
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and CT scan assessment of benign versus fatal spontaneous cerebellar haematomas

Abstract: We have studied 15 cases of spontaneous intracerebellar haematomas in 9 males and 6 females. A significant correlation between the clinical presentation and the CT scan features of benign and fatal haemorrhages of the cerebellum is presented. Diagnostic computerized tomographic studies were performed in a mean interval of 31 hours after the initial symptoms. 60% were diagnosed and treated in less than 24 hours; 11 patients had haematomas larger than 3 cm, and 5 (45%) of these cases died with evidence of irreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
8

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
1
15
0
8
Order By: Relevance
“…However, no evidence exists that outcome in elderly patients following a cerebellar hematoma is particularly poor, and thus, it may be premature in the elderly patient to conclude that decompressive craniectomy and hematoma evacuation are unrealistic interventions. This observation may partially explain the close association of old age with poor outcome in several earlier studies in smaller groups of patients with cerebellar hematoma [5, 12]. …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, no evidence exists that outcome in elderly patients following a cerebellar hematoma is particularly poor, and thus, it may be premature in the elderly patient to conclude that decompressive craniectomy and hematoma evacuation are unrealistic interventions. This observation may partially explain the close association of old age with poor outcome in several earlier studies in smaller groups of patients with cerebellar hematoma [5, 12]. …”
Section: Discussionmentioning
confidence: 68%
“…Important clinical variables might be age, deterioration in clinical condition, coma, and at the extreme, clinical signs of pontine compression, such as a forced gaze and pinpoint pupils [10]. Neuroradiological features that may persuade neurosurgeons to evacuate the hematoma are size, presence of hydrocephalus and perhaps most commonly distortion of the brainstem [10, 11, 12, 13, 14]. Little et al [11]reported, after CT scan became in common use, that medical management can be considered when a hematoma is less than 3 cm in diameter, and obstructive hydrocephalus or ventricular extension is absent.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly good results have been reported with surgical evacuation of cerebellar haematomas, but the optimal timing has not been established, and there are no prospective RCTs of surgery in cerebellar haemorrhage. By contrast there is universal clinical agreement for ventricular drainage for hydrocephalus at any time after ictus [131]. For this reason ventricular drainage and evacuation of the cerebellar haematoma should be considered if hydrocephalus occurs or if haematomas are >2–3 cm in diameter, although advanced age and coma militate against favourable outcomes.…”
Section: Specific Treatmentmentioning
confidence: 99%
“…Despite the advantage of early diagnosis by CT and the advances in microneurosurgical technique, the mortality rates were reduced signifi cantly and clinical deterioration occurred frequently in the course of the disease, regardless of the therapeutic regimen. Several authors [10][11][12] stressed the importance of the clinical symptoms for indicating prognosis and observed a rapid progressive deterioration in one group and a more benign stable course in another group; however, this differ ence did not correlate well with the extent of the hematoma in the CT [4,13]. The specific location of the hematoma within the cerebellum plays some role, so that a laterodorsal site promises, according to Sala zar et al [13], a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors [10][11][12] stressed the importance of the clinical symptoms for indicating prognosis and observed a rapid progressive deterioration in one group and a more benign stable course in another group; however, this differ ence did not correlate well with the extent of the hematoma in the CT [4,13]. The specific location of the hematoma within the cerebellum plays some role, so that a laterodorsal site promises, according to Sala zar et al [13], a better outcome. Of great importance are, consistent with our findings, CT features which Taneda et al [14] noted as the presence of cisternal compression, in particular of the quadrigeminal and vermian cistern.…”
Section: Discussionmentioning
confidence: 99%